Prevalence of Enterobiasis Infection Among School-Aged Children in the Kebon Kongok Landfill Area, West Lombok - Adelia Riezka Rahim; Nurmi Hasbi; Rosyunita Rosyunita; Eva Triani; Wayan Sulaksmana Sandhi Parwata (Jurnal Penelitian Pendidikan IPA, 2023)
Enterobiasis, also known as pinworm infection, is a parasitic infestation that predominantly affects children and is caused by the Enterobius vermicularis parasite. Worm infections can significantly impact an individual's productivity and immune system. This study aims to document the occurrence of enterobiasis among children aged 6 to 9 years in the Kebon Kongok landfill area of West Lombok Regency. Data collection involved the administration of the cellophane tape method and a questionnaire filled by the parents or guardians of the participating children. Among the 188 participants, 36 children (19.15%) were identified as having enterobiasis. Notably, boys exhibited a higher prevalence than girls, and the most common age for enterobiasis was 7 years. Statistical analysis revealed that the child's age, their habit of playing in the dirt, and the parents' or guardians' age are pivotal factors influencing the incidence of enterobiasis in the Kebon Kongok landfill area of West Lombok Regency.